Entrainment and mixing layer oscillations induced by a flow beneath a rectangular compartment - Chua, Lloyd Hock Chye. (2009)
The present study investigates the entrainment characteristics and feedback mechanisms causing periodic mixing layer oscillations associated with a flow stream beneath a rectangular compartment. The entrainment studies were based on mixing rate measurements in rectangular and circular storage tanks from two previous studies. An approximate unified equation for predicting the entrainment rate across a density interface, in both rectangular and circular storage tanks, induced by a flow stream below the tank, was derived. The results show that under equivalent conditions, the mixing rates in a circular tank is higher than in a rectangular tank, probably an indication of more complex 3-D flow patterns inside a circular tank as compared to the 2-D flow patterns inside a rectangular tank.